Synthesis of zinc oxide nanoparticles and their potential application in the detection of latent fingerprints - Flores Mariños, Betty Mercedes; Guzman, Maribel; Grieseler, Rolf; Quiroz Chang, Aransselly Jesús; Malet, Loic; Godet, Stephane (Springer Nature, 2025)
Zinc oxide in nanometric dimensions, thanks to its optical properties, is an oxide of great interest for its potential use as a revealing agent for latent fingerprints. In this article we present the synthesis and characterization of ZnO nanoparticles obtained by two methods and it uses in revealing of latent fingerprints on non-porous surfaces. The nanoparticles synthetized present an atomic Zn:O ratio of 0.99 and 1.15 when precipitation and combustion in solution method were used, respectively. Both samples show a hexagonal arrangement (wurtzite) according to the X-ray diffraction and Raman spectra. Raman results show a shift at 439 cm−1 corresponding to the E2 (high) mode of the ZnO crystalline hexagonal wurtzite structure. Transmission electron microscopy images show that nanoparticles with smaller average diameters are obtained by chemical precipitation (17.2 ± 10.8 nm) than combustion in solution (73.4 ± 6.0 nm). Samples presented a narrow band gap of 3.69 and 3.59 eV, values higher than that reported for the bulk material (3.37 eV). The photoluminescence spectrum showed a characteristic ultraviolet emission peak around 387 nm and green emissions peaks from ZnO when excitation wavelength of 325 and 488 nm were experiment, respectively. Finally, ZnO nanoparticles were used to reveal latent fingerprints on non-porous surfaces using a 325 nm laser. Fingerprint development is better on black glass surface when using precipitated ZnO. However, Fingerprints are better observed in aluminum foil when ZnO obtained by combustion in solution is applied. The results show that it is possible to use ZnO nanoparticles obtained by both methods as latent fingerprint revealing agents.
Keywords: Dactiloscopia; Nanopartículas; Fotoluminiscencia; Óxido de cinc; https://purl.org/pe-repo/ocde/ford#2.04.01